Amphibians and Reptiles Survey at Tasik Pergau, Jeli, Kelantan and Its Updated Checklist - Ngadi E.; Hambali K.; Mohamed M.S.; Abdul Wahab M.A.I.; Nor S.M. (IOP Publishing Ltd, 2024)
Indexed by Scopus